Periodontal Inflamed Surface Area Is Associated With Increased Gestational Blood Pressure and Uric Acid Levels Among Pregnant Women From Rural North China - Hu, Shaonan; Yu, Feifan; Jiang, Hong; Shang, Wei; Miao, Hui; Li, Simin; Zhao, Jianjiang; Xiao, Hui (Frontiers in Cardiovascular Medicine, 2022)
Background: Periodontal disease has been associated with gestational complications and both conditions have a high prevalence in rural populations from developing regions. A cross-sectional study was carried out to explore the relationship between periodontal inflamed surface area (PISA), blood pressure (BP), and, serum uric acid levels (UA) in a group of rural North Chinese pregnant women in the third trimester of pregnancy. Methods: 335 rural women aged 20-34 years, with normal BMI were examined in a cross-sectional study during their third trimester of gestation. Exclusion criteria were history of pregnancy complications, multiple pregnancy, tobacco use, diabetes, hypertension or any infectious disease. Socio-demographic variables, including age and socioeconomic status (SES), systolic (SBP) and diastolic (DBP) blood pressure readings, serum UA levels, and PISA values were recorded. A structural equation model was implemented with two constructed latent variables including ‘Dem’ (comprising of Age and SES category to represent unobserved demographic variables) and, ‘BP’ (comprising of SBP and DBP to account for measurement error and lack of multiple BP readings). The model accounted for co-variance of BP and UA, and implemented simultaneous regressions for BP and UA as outcomes, upon Dem and PISA values as exogenous variables. Results: The median PISA score was 1081.7 (IQR=835.01), reflecting high levels of periodontal inflammation in the sample. SEM showed a significant association of PISA with BP (estimate=0.011, 95% CI= 0.009-0.012 p<0.001) and UA (estimate=0.001, 95% CI= 0.001-0.001, p<0.001). Conclusion: Higher PISA values were significantly associated with higher blood pressure and uric acid levels among rural pregnant women in a cross-sectional sample from a center in North China after accounting for a latent demographic construct derived from age and SES. Keywords: Periodontal Disease, low birth weight, Gestational Hypertension, Uric Acid, periodontal inflamed surface area